2015
DOI: 10.17219/acem/33841
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on J-Resolved NMR Method Usability for Toxic Kidney's Injury Assessment

Abstract: Background. Nowadays, the Nuclear Magnetic Resonance (NMR) techniques are tested for metabolomic urine profile in order to detect early damage of kidney. Objectives. The purpose of this investigation was the initial assessment of two-dimensional J-resolved NMR urine spectra analysis usability for early kidney injuries detection. The amino acids (AA) and acids profile change after the exposure to nephrotoxic agent (the cisplatin infusion) was examined. Material and Methods. The material was the urine of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…38 Lactate/pyruvate ratio and LDH levels increased from No-NRP to 2 hours NRP, likely due to the metabolism disturbances of WI, 39,40 suggesting ischemic impairment. 41,42 These markers returned to basal values between 4 and 6 hours NRP, suggesting a better balance in supply and demand in organ perfusion and an efficient adjustment of tissue oxygenation and adequate perfusion. Collectively, these markers are related to tissue hypoperfusion, but the observed return to normal values highlights the potential benefits of NRP in re-establishing sustained aerobic metabolism, supporting the reconditioning role of NRP through maintenance of oxygenated blood circulation and normothermia.…”
Section: Early and Late Kidney Functions Were Improved By 4 H To 6 mentioning
confidence: 89%
See 1 more Smart Citation
“…38 Lactate/pyruvate ratio and LDH levels increased from No-NRP to 2 hours NRP, likely due to the metabolism disturbances of WI, 39,40 suggesting ischemic impairment. 41,42 These markers returned to basal values between 4 and 6 hours NRP, suggesting a better balance in supply and demand in organ perfusion and an efficient adjustment of tissue oxygenation and adequate perfusion. Collectively, these markers are related to tissue hypoperfusion, but the observed return to normal values highlights the potential benefits of NRP in re-establishing sustained aerobic metabolism, supporting the reconditioning role of NRP through maintenance of oxygenated blood circulation and normothermia.…”
Section: Early and Late Kidney Functions Were Improved By 4 H To 6 mentioning
confidence: 89%
“…HO-1 expression attenuates IRI and improves survival in rat renal allografts 37. Lactate/pyruvate ratio and LDH levels increased from No-NRP to 2 hours NRP, likely due to the metabolism disturbances of WI,39,40 suggesting ischemic impairment 41,42. Lactate/pyruvate ratio and LDH levels increased from No-NRP to 2 hours NRP, likely due to the metabolism disturbances of WI,39,40 suggesting ischemic impairment 41,42.…”
mentioning
confidence: 99%
“…In cancer treatment with cDDP, metabolomics has been applied to several human cancer cell lines in search of biomarkers of chemotherapy efficacy (lung [10,11], breast [12,13], bone [14,15], brain [16], and ovarian [17,18]) or resistance (ovarian [17,18,19], ovarian and lung [20], breast [21]). CDDP treatment efficacy and nephrotoxicity have also been assessed through kidney tissue metabolomics in a mouse model of metastatic melanoma [22], and biofluids, namely serum/plasma [23,24,25] and urine [26], in a model of lung cancer, both for cDDP sole [24,25] and combined administration [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous human AKI studies resulted in the identification of a variety of potential metabolite biomarkers [14,24]. Interestingly, almost no overlap exists between the respective metabolites [28][29][30][31][32][33][34] and the metabolites identified in our study. For example, Beger et al identified homovanillinic acid sulfate, a dopamine metabolite as the most important marker in the urine of children who developed AKI after cardiac surgery [21].…”
Section: Discussionmentioning
confidence: 47%